Lack of early inbreeding depression and distribution of selfing rates in the neotropical emergent tree Ceiba pentandra: Assessment from several reproductive events - Lobo Segura, Jorge Arturo (2015)
Premise of the study: Selfing and mixed mating systems are prevalent in many flowering plants. Purging of genetic load can occur in these species, reducing negative effects of selfing. Long‐term studies of the temporal and spatial variation of selfing rates and inbreeding depression at the individual level are necessary to understand the forces that maintain selfing as a mating strategy in these species. Methodology: We used microsatellites to estimate selfing rates in seeds and seedlings over 6 years in a population of Ceiba pentandra in southwestern Costa Rica. We studied the correlation of selfing with early seedling vigor variables to test for inbreeding depression. Key results: Selfing rates varied widely among maternal trees. However, we found high consistency of selfing rates for individuals among years. Selfing rate did not influence early fitness traits, suggesting a lack of inbreeding depression at this stage. Maternal effects were a predominant source of variation for early vigor variables. Conclusions: Variability in selfing rates among trees may be partly explained by genetic variation in a late‐acting self‐incompatibility system or low, early‐acting genetic load in some individuals. This population did not show evidence of early inbreeding depression in traits related to seed vigor probably from complete or partial purging as a result of repeated selfing of a fraction of the population or from strong maternal effects. Expression of genetic load at later developmental stages or in more stressful natural conditions may explain differences in inbreeding levels between seeds and adults.